Pengaruh lama penyimpanan kolostrum sapi pada suhu beku terhadap pH, total bakteri, dan konsentrasi immunoglobulin G - Annisa Putriani; Eka Wulandari; Raden Febrianto Christi (Fakultas Pertanian Universitas Majalengka, 2024)
Colostrum is a thick yellow liquid whose role is to provide the first nutrition to the calf as a passive immune transfer, so, it must always be available. Frozen colostrum is one of the efforts used to extemd the shelf life by providing colostrum reserves. Frozen colostrum doesn’t always maintain good colostrum quality, sometimes it causes a decrease in the colostrum quality. This research aim to analyzed the effect of freezing storage bovine colostrum on pH, total bacteria, and immunoglobulin levels. This research was using a Completely Randomized Design (CRD) with 5 long storage treatments (P1 (Day-0), P2 (Day-7), P3 (Day-14), P4 (Day-21), dan P5 (Day-28) dan 4 repetition. The data obtained were analyzed by Anova and Ortogonal Polinomial tests. The result showed that freezing storage (-28° C) bovine colostrum had an effect on decrease in pH and had the quartz regression pattern in the equation Y = 0,000007 + 0,0105 – 0,0973 6,7075 with a determination coefficient of = 0,9739. Meanwhile, it hadn’t effect on total bacteria and immunoglobulin G levels, so it hadn’t respons and pattern of polinomial ortogonal. It can be concluded that the average each treatments of pH, total bacteria, and IgG levels is still classified as good quality.